Increased Seroprevalence and Improved Antibody Responses Following Third Primary SARS-CoV-2 Immunisation: An Update From the COV-AD Study - Shields, Adrian M.; Faustini, Sian E.; Hill, Harriet J.; Al-Taei, Saly; Tanner, Chloe; Ashford, Fiona; Workman, Sarita; Moreira, Fernando; Verma, Nisha; Wagg, Hollie; Heritage, Gail; Campton, Naomi; et al. (Frontiers in Immunology, 2022)
Background Patients with primary and secondary antibody deficiency are vulnerable to COVID-19 and demonstrate diminished responses following two-dose SARS-CoV-2 vaccine schedules. Third primary vaccinations have been deployed to enhance their humoral and cellular immunity. Objectives To determine the immunogenicity of the third primary SARS-CoV-2 immunisation in a heterogeneous cohort of patients with antibody deficiency. Methods Participants enrolled in the COV-AD study were sampled before and after their third vaccine dose. Serological and cellular responses were determined using ELISA, live-virus neutralisation and ELISPOT assays. Results Following a two-dose schedule, 100% of healthy controls mounted a serological response to SARS-CoV-2 vaccination, however, 38.6% of individuals with antibody deficiency remained seronegative. A third primary SARS-CoV-2 vaccine significantly increased anti-spike glycoprotein antibody seroprevalence from 61.4% to 76.0%, the magnitude of the antibody response, its neutralising capacity and induced seroconversion in individuals who were seronegative after two vaccine doses. Vaccine-induced serological responses were broadly cross-reactive against the SARS-CoV-2 B.1.1.529 variant of concern, however, seroprevalence and antibody levels remained significantly lower than healthy controls. No differences in serological responses were observed between individuals who received AstraZeneca ChAdOx1 nCoV-19 and Pfizer BioNTech 162b2 during their initial two-dose vaccine schedule. SARS-CoV-2 infection-naive participants who had received a heterologous vaccine as a third dose were significantly more likely to have a detectable T cell response following their third vaccine dose (61.5% vs 11.1%). Conclusion These data support the widespread use of third primary immunisations to enhance humoral immunity against SARS-CoV-2 in individuals with antibody deficiency.